Cellular Localization of Activated Factor X by Xa-Specific Probes - Zacharski, Leo R; Dunwiddie, Christopher; Nutt, Elka M; Hunt, Jane; Memoli, Vincent A (Thrombosis and Haemostasis, 1991)
A probe, recombinant antistasin, that reacts specifically with the activated form of factor X (Xa) was used in immunohistochemical procedures to detect cellular sites of Xa generation within intact tissues. Factor Xa was detected on tumor cells in small cell carcinoma of the lung, renal cell carcinoma, and malignant melanoma. Tumor-associated macrophages (but not tumor cells) expressed Xa in adenocarcinoma and squamous cell carcinoma of the lung, and Hodgkin’s disease. Factor Xa in these locations corresponded to evidence reported previously for an intact coagulation pathway and thrombin formation associated with these tumor cells and macrophages. By contrast, only rare connective tissue cells stained for Xa in breast and colon cancer, tumor types shown previously to lack an intratumoral coagulation pathway and thrombin generation, and in normal liver, lung, breast, kidney, and placental tissues. Hepatocytes did not stain. These results suggest that such probes may be useful for studying the activation state of cell-associated factor X in situ within intact tissues.